A Tb and Ag co-doped borate compound forms a high sensitive X-ray, gamma-ray and neutron luminescence dosimeter. Issue 13 (17th March 2023) - França, Leonardo V. S.; Müller, Elisabeth; Yukihara, Eduardo G.; Baffa, Oswaldo
Abstract : Thermal and optical stimulations of neutron-sensitive CaB6 O10 :Tb 3+, Ag + led to two recombination pathways. Abstract : Space, radiotherapy, X-ray imaging/screening, nuclear reactors, large research facilities (linear accelerators and synchrotron radiation facilities) and nuclear accidents are all examples associated with the need for monitoring high-energy radiation. Herein, we report the luminescent and dosimetric properties of a radiation sensitive phosphor based on CaB6 O10 :Tb 3+, Ag + compounds. The operation principle here is the optically stimulated luminescence (OSL), which is the luminescence of a previously irradiated material under optical stimulation. The phosphor presented strong UV-OSL under blue stimulation (a minimum detectable dose of 2.3 μGy), with dose linearity in the whole dose range analysed (30 mGy–20 Gy) and no signs of saturation. The thermoluminescence (TL) of the phosphor featured mainly a peak at 275 °C, whose trapping center was shown to be associated with the main OSL component. Furthermore, the TL emission is dominated by Tb 3+ emission lines (main emission at 541 nm). Overcoming the main limitation of the commercial Al2 O3 :C phosphor, OSL was observed after neutron irradiation. Besides reporting the luminescent and dosimetric properties of a novel neutron sensitive OSL phosphor obtained through a low-cost synthesis method, this work sheds light on how lanthanide and silver ions influence the charge trapping and radiative processes in borate compounds.